Curriculum development based on Iddhipada 4 for school administrators in Nakhon Sawan Primary Education Area 1: - - Aonlamoon , Jakkol; Metheevachatra, Anond; Thuenchang, Worrakrit (Mahachula Academic Journal, 2026)
Abstract This research aimed to: (1) study the conditions of school curriculum development by school administrators under the Nakhon Sawan Primary Educational Service Area Office 1; (2) develop guidelines for school curriculum development based on the Four Bases of Success (Iddhipada IV) for school administrators under the Nakhon Sawan Primary Educational Service Area Office 1; and (3) evaluate the guidelines for school curriculum development based on the Four Bases of Success (Iddhipada IV) for school administrators under the Nakhon Sawan Primary Educational Service Area Office 1. This study employed a mixed-methods research design consisting of both qualitative and quantitative approaches and was conducted in three phases. Phase 1 focused on studying the conditions of school curriculum development. The sample group consisted of 161 participants, including school administrators and heads of academic affairs departments. The research instrument was a questionnaire on the conditions of school curriculum development by school administrators under the Nakhon Sawan Primary Educational Service Area Office 1, with a reliability coefficient of 0.96. The statistics used for data analysis were percentage, mean, and standard deviation. Phase 2 aimed to develop guidelines for school curriculum development based on the Four Bases of Success (Iddhipada IV) for school administrators. This phase employed qualitative research methods. Data were collected through focus group discussions with 9 key informants. The research instrument was a draft of the guidelines for school curriculum development based on the Four Bases of Success (Iddhipada IV) for school administrators. Data were analyzed using content analysis. Phase 3 involved evaluating the guidelines for school curriculum development based on the Four Bases of Success (Iddhipada IV) for school administrators. Data were collected from a target group consisting of 15 school administrators and 1 deputy director of the Primary Educational Service Area Office. The research instrument was an evaluation form. The statistics used for data analysis were mean and standard deviation. The research findings revealed that : (1)The overall conditions of school curriculum development by school administrators under the Nakhon Sawan Primary Educational Service Area Office 1 were at the highest level (X̄ = 4.68, S.D. = 0.47). When considering each aspect, the aspect with the highest mean score was the determination of school curriculum objectives, which was at the highest level (X̄ = 4.71, S.D. = 0.45), followed by the development of the school curriculum (X̄ = 4.67, S.D. = 0.47), and the implementation of the school curriculum (X̄ = 4.67, S.D. = 0.47). The aspect with the lowest mean score was the evaluation, improvement, and development of the school curriculum, which was also at the highest level (X̄ = 4.66, S.D. = 0.48). (2) The guidelines for school curriculum development based on the Four Bases of Success (Iddhipada IV) for school administrators under the Nakhon Sawan Primary Educational Service Area Office 1 consisted of 4 aspects with a total of 16 guidelines: 1) determination of school curriculum objectives, comprising 4 guidelines; 2) development of the school curriculum, comprising 4 guidelines; 3) implementation of the school curriculum, comprising 4 guidelines; and 4) evaluation, improvement, and development of the school curriculum, comprising 4 guidelines.(3)The evaluation results of the guidelines for school curriculum development based on the Four Bases of Success (Iddhipada IV) for school administrators under the Nakhon Sawan Primary Educational Service Area Office 1 revealed that the overall evaluation was at the highest level (X̄ = 4.59, S.D. = 0.47). When considering each aspect, accuracy was at a high level (X̄ = 4.44, S.D. = 0.50), feasibility was at the highest level (X̄ = 4.52, S.D. = 0.50), appropriateness was at the highest level (X̄ = 4.68, S.D. = 0.45), and usefulness was at the highest level (X̄ = 4.73, S.D. = 0.45). Keywords: Curriculum development; The Four Bases of Success (Iddhipada IV); School administrators